Bioinspired Freeze‐Tolerant Soft Materials: Design, Properties, and Applications. Issue 37 (15th August 2022) - Wang, Zhiyong; Valenzuela, Cristian; Wu, Jianhua; Chen, Yuanhao; Wang, Ling; Feng, Wei
Abstract: In nature, many biological organisms have developed the exceptional antifreezing ability to survive in extremely cold environments. Inspired by the freeze resistance of these organisms, researchers have devoted extensive efforts to develop advanced freeze‐tolerant soft materials and explore their potential applications in diverse areas such as electronic skin, soft robotics, flexible energy, and biological science. Herein, a comprehensive overview on the recent advancement of freeze‐tolerant soft materials and their emerging applications from the perspective of bioinspiration and advanced material engineering is provided. First, the mechanisms underlying the freeze tolerance of cold‐enduring biological organisms are introduced. Then, engineering strategies for developing antifreezing soft materials are summarized. Thereafter, recent advances in freeze‐tolerant soft materials for different technological applications such as smart sensors and actuators, energy harvesting and storage, and cryogenic medical applications are presented. Finally, future challenges and opportunities for the rapid development of bioinspired freeze‐tolerant soft materials are discussed. Abstract : Many biological organisms in nature show an exceptional antifreezing ability to survive in extremely cold environments. This review provides a state‐of‐the‐art account of bioinspired freeze‐tolerant soft materials and their emerging technological applications. The perspectives for future challenges and opportunities to develop innovative antifreezing materials are addressed.